2020
DOI: 10.1097/qai.0000000000002232
|View full text |Cite
|
Sign up to set email alerts
|

Use of HIV Pre-exposure Prophylaxis (PrEP) Associated With Lower HIV Anxiety Among Gay and Bisexual Men in Australia Who Are at High Risk of HIV Infection: Results From the Flux Study

Abstract: Background: Many gay and bisexual men (GBM) experience HIV anxiety, particularly around condomless anal intercourse. HIV pre-exposure prophylaxis (PrEP) is an effective HIV prevention strategy that may reduce HIV anxiety among GBM. Methods: The Following Lives Undergoing Change (Flux) Study is a national, online, open-prospective observational study of licit and illicit drug use among GBM in Australia. In 2018, participants responded to newly included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 40 publications
5
28
0
Order By: Relevance
“…PrEP users reported an increase in quality of their sex lives, and, to a lesser extent, an increase in quality of life in general. Similar to earlier studies (Collins et al, 2017;Hojilla et al, 2016;Keen et al, 2020;Koester et al, 2017;Moeller et al, 2020;Whitfield et al, 2019), PrEP users also reported less fear of HIV when having sex since they started using PrEP. This reduced fear was positively related to improvements in quality of sex life.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…PrEP users reported an increase in quality of their sex lives, and, to a lesser extent, an increase in quality of life in general. Similar to earlier studies (Collins et al, 2017;Hojilla et al, 2016;Keen et al, 2020;Koester et al, 2017;Moeller et al, 2020;Whitfield et al, 2019), PrEP users also reported less fear of HIV when having sex since they started using PrEP. This reduced fear was positively related to improvements in quality of sex life.…”
Section: Discussionsupporting
confidence: 82%
“…While it has been suggested that PrEP may have benefits for the quality of sex life in addition to its benefits for HIV prevention (Calabrese & Underhill, 2015;Grant & Koester, 2016;Race, 2016), there are only a limited number of studies that investigated the quality of sex life of PrEP users and what factors are related to their quality of sex life. One of these factors could be reduced fear of HIV as it has been found that PrEP reduces HIV-related fear (Collins et al, 2017;Hojilla et al, 2016;Keen et al, 2020;Koester et al, 2017;Moeller et al, 2020;Whitfield et al, 2019). The reduced fear of HIV could lead to less consistent condom use, which in turn has been related to improvements in quality of sex life as well (Carballo-Diéguez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of formal PrEP use have also highlighted reduced fear of HIV, and improved sexual satisfaction and well-being [17,50]. Similar findings have been obtained in studies of PrEP in non-clinical settings as well as in relation to informal PrEP use, including decreased condom use, reduced fear of HIV, and improved quality of sex life [27,51,52]. Informal PrEP use has also been associated with other increases in risk behavior, including recreational drugs use and group sex [11].…”
Section: Sexual Behavior and Well-beingsupporting
confidence: 52%
“…Although in our study we found no significant association between anxiety or depression and reporting recent PrEP use or PrEP, in a 2020 Australian study, PrEP use was independently associated with lower levels of HIV-related anxiety among PrEP-eligible men (MSM at high risk of HIV infection) than among PrEP ineligible men (MSM at low risk). 20 Alongside the increase in PrEP use, we found a substantial decreasing trend in PEP use between 2013 and 2018, and that the use of PEP was a predictor of future PrEP initiation. This finding suggests that transition from PEP use to PrEP use occurred in these men.…”
Section: Discussionmentioning
confidence: 71%
“…Although in our study we found no significant association between anxiety or depression and reporting recent PrEP use or PrEP, in a 2020 Australian study, PrEP use was independently associated with lower levels of HIV-related anxiety among PrEP-eligible men (MSM at high risk of HIV infection) than among PrEP ineligible men (MSM at low risk). 20 …”
Section: Discussionmentioning
confidence: 99%